1996
DOI: 10.1021/jp961220v
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Order of DMPC sn-1 versus sn-2 Chains and Membrane Thickness:  An Approach to Molecular Protrusion by Solid State 2H-NMR and Neutron Diffraction

Abstract: The ordering properties of sn-1 and sn-2 dimyristoylphosphatidylcholine (DMPC) chains are investigated by NMR and neutron diffraction in order to relate membrane defects to bilayer thickness. First, the effect of temperature and 30 mol % cholesterol on DMPC membranes perdeuterated on the sn-1 acyl chain is studied by solid state 2 H-NMR. Using the concept of C-C bond order parameters, S CC , a comparison is made between both lipid chains according to our previously published data on sn-2 chains (Douliez; et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
64
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 41 publications
23
64
0
Order By: Relevance
“…This alternating pattern is also visible in the S CH (C n ) curves for these two phases, most pronounced for the LC phase. A similar pattern has been reported as the odd-even effect in the context of carbon order parameters S CC for the DPPC system [29] and for other lipids [99,102]. A decrease of the odd-even effect toward the end of the tail [29], as well as an increase of this effect with increasing temperature [99,102] were also reported.…”
Section: Dihedral-angle Conformationssupporting
confidence: 82%
See 1 more Smart Citation
“…This alternating pattern is also visible in the S CH (C n ) curves for these two phases, most pronounced for the LC phase. A similar pattern has been reported as the odd-even effect in the context of carbon order parameters S CC for the DPPC system [29] and for other lipids [99,102]. A decrease of the odd-even effect toward the end of the tail [29], as well as an increase of this effect with increasing temperature [99,102] were also reported.…”
Section: Dihedral-angle Conformationssupporting
confidence: 82%
“…A similar pattern has been reported as the odd-even effect in the context of carbon order parameters S CC for the DPPC system [29] and for other lipids [99,102]. A decrease of the odd-even effect toward the end of the tail [29], as well as an increase of this effect with increasing temperature [99,102] were also reported. The effect was explained in these studies as predominantly arising from the alternation of bond-vector orientations relative to the bilayer normal in a nearly all-trans conformation.…”
Section: Dihedral-angle Conformationssupporting
confidence: 82%
“…We deduce from our data that these biological vesicles are very fluid even at low temperatures. PI provides a greater chain disorder of the membrane, which may result in a reduction of the membrane thickness (21,22). This effect could be promoted both by the PI head group and chains.…”
Section: Discussionmentioning
confidence: 99%
“…Because the membrane ordering is directly linked to bond or molecule space averages, it can be translated, using an appropriate theory, to average length of a molecule in a membrane and hence to membrane thickness (Fig. 2d) [13,14]. It is shown that increase/ decrease in bilayer order means increase/decrease in membrane thickness.…”
Section: Cholesterolmentioning
confidence: 99%